Frequency of Benign and Malignant ovarian tumours in a tertiary Care hospital. - Yasmin, Sumaira; Yasmin, Aiman; Asif, Muhammad (Journal of Postgraduate Medical Institute, 2011)
To find out frequency of benign and malignant ovarian tumours in a single unit in a period of one year. This was a descriptive cross sectional hospital based study conducted in gynae A unit LRH, peshawar from first January to December 2002. Patients with ovarian tumours were admitted followed by a detailed case history and thorough clinical examination. all the relevant details were recorded on a questionnaire. Patients were investigated and after performing surgery. the specimens of ovarian tumours taken were subjected to histopathological examination in the pathology department LRH, Peshawar. ovarian tumour constitute a significant proportion of gynaecological admissions with benign tumours being more freqeunt than malignant ones.